Peran Penilaian Autentik Terhadap Peningkatan Kualitas Pendidikan di Sekolah Dasar: Peran Penilaian Autentik Terhadap Peningkatan Kualitas Pendidikan di Sekolah Dasar - Qiftiyah, Maratul; Kasmudi (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2023)
Learning evaluation is an integral part of education which functions to measure student learning outcomes, assess the success of learning programs, and provide input for improving the teaching and learning process. Overall, learning evaluation has a positive impact in improving the quality of education. The results of the review show that the implementation of planned and sustainable learning evaluations, with valid instruments and authentic assessments, has been proven to be able to make a real contribution to improving the overall quality of schools. Teachers can improve the quality of learning because learning improvements can be made when weaknesses or deficiencies in the learning process are known in detail from the results of good learning evaluations. Therefore, learning evaluation is an essential component to achieve optimal educational quality.